(3GdefJNH aj GdSjGSI hGdBOGHs - (3CHj GdaJM fGUQ Hf YHO GdSjO Hf GdWQRj,J (B610 (3g` s ((3Ydi Hf CMeO GdTGOi GdcThWi s)
(3ChdgG (B:s
(3GdMeO ddg hMOg hHYO aEf CHhGH gPG GdcJGH GdefJNH ai GdSjGSI hGdCOH NeSI hCQHYhf HGHG s
(3BNQgG (B:s
(3ef bUI YLhR eQjVI YGOI WHjH (B: (3abGd (B: (3eG CMhL gPg Edi RhL aGfJgQg hdOgG , hbGd dg (B: (3GfXQ ajeG jUdM hOY eGdGjYfjc aVMc GdWHjH hGfUQa s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(91(3b(B) s
Keywords: (3GdCOHs